Comparison of pulmonary function test results before and after exercise in junior high school students - Hendy Zulkarnain; Munar Lubis; Gabriel P.; Ridwan M. D.; Helmi M. Lubis (Indonesian Pediatric Society, 2010)
Background During exercise, bronchoconstriction occurs dueÂ to heat loss from mucosal respiratory ract. Exercise test canÂ be performed to evaluate hyper-reactivity of the bronchus. TheÂ examination of pulmonary function is beneficial to confinn theÂ diagnosis, to determine precipitating factors, and to evaluateÂ disease severity and therapeutic response.Objective To compare pulmonary function test values before andÂ after exercise in junior high school students aged 13 to 15 years.Methods Experimental study of 60 junior high school studentsÂ from Bilah Hulu was performed using spirometry to evaluateÂ pulmonary function before and after eight minutes of exercise.Â Results Functional vital capacity (FVC) values before and afterÂ eightô€…minute exercise were 2.20 (SD 0.52) and 2.18 (SD 0.42),Â respectively. There was no significant difference between FVCÂ values before and after exercise (P>0.05). The mean forcedÂ expiratory volume in 1 second (FEV 1) values before and aftereight minutes of exercise were 2.21 (SD 0.42) and 2.13 (SD 0.50)Â respectively. There was no significant difference between FEV 1Â before and after the exercise (P>0.05).Conclusion Eightô€…minute exercise does not influence theÂ pulmonary function test results in healthy children.